Concurrent Detection of Circulating Tumor Cells and Circulating Tumor DNA in Triple-negative Breast Cancer - Gomez, Henry L; Castaneda, Carlos A.; Castillo, Miluska; Reuben, James; Gao, Hui; Suarez, Nnacy; Bernabe, Luis A.; Cotrina, Jose M.; Dunstan, Jorge; Velarde, Marco; et al. (Asian Pacific Journal of Cancer Care, 2021)
Objective: Circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) provide tumor information in breast cancer. Our objective was to characterize CTCs, and contrasted them with ctDNA PIK3CA mutation in 24 triple-negative breast cancer (TNBC). Methods: CTCs genes were characterized by AdnaTest protocol and ctDNA by digital PCR. Results: We found CTCs genes in 37.5% and ctDNA PIK3CA mutations in 29.16%. Three cases with CTCs genes had concurrent ctDNA PIK3CA mutations. MUC1 or GA733-2 were found in 4 cases, and 3 of them had concurrent ctDNA PIK3CA. CTCs ALDH1/TWIST1 were found in 2 cases, AKT2 in one and PI3Kα in another, and none had concurrent ctDNA PIK3CA mutations. There was no correlation between CTCs and ctDNA detection. All 3 cases with CTC & cDNA concurrent finding underwent death during follow-up. Conclusion: Infrequent concurrent detection of CTC and ctDNA presence suggests that both represent independent processes in TNBC patients, and could identify worst prognosis cases.